Suggesting Some Criteria for The Foundations of Oil Tanks - Salih, Salah M. (Journal of Petroleum Research and Studies, 2025)
The tank foundation serves as a support base for oil tanks, ensuring their stability by withstanding the tank's weight. Foundation failure commonly occurs when it cannot support the tank's weight or when the soil's bearing capacity cannot resist the stress imposed by the tank and its foundation. This study aims to ensure the stability of the tank-foundation system by selecting an appropriate foundation system that considers the soil's bearing capacity. The deformation behavior of slab-foundations for tank foundations under different conditions, with the objective of determining the optimal design for such foundations was investigated. The models used in the study are based on previous research and employ finite element analysis using STAAD Pro Foundation CONNECT Edition V.9 software to assess the stability of the structure-foundation system. The study examines three different types of foundation systems, considering parameters such as thickness, bearing capacity, and elasticity. Results indicate that the raft foundation is the most optimal design for stiff residual soils, the pile-raft structure-foundation is most suitable for marine sediment deposits, and the pile foundation is highly recommended for soft peaty soils. Finally, this research presents a specific process for determining the features of slab foundations according to soil factors and variables, which can be used to select better designs for oil tank foundations.